Sarf Ibtida’iy Assessment with Opexams Among University Students Based on Artificial Intelligence - Setiawan, Akhmad Yusuf Isnan; Inayah, Inayah; Muhtar, Muhammad Izzul; Saputra, Feri Aditia; Abu Samra, Asma’ Na’im Jamil (Institut Agama Islam Negeri Palangka Raya, 2024)
This study aims to characterize Opexams and evaluate their effectiveness on the learning outcomes of shart-ibtida